The effect of horticultural therapy on depressive symptoms among the elderly: A systematic review and meta-analysis - Zhang, Ya Wei; Wang, Jun; Fang, Tian Hong (Frontiers in Public Health, 2022)
Objective: This systematic review and meta-analysis aimed to assess the strength of the effect of horticultural therapy on depressive symptoms among the elderly, and to determine the potential moderators of the intervention effect. Methods: Randomized controlled trials and Quasi-experimental studies were searched on Web of Science, PsycINFO, CINAHL, EMBASE, Medline, PubMed, CNKI, WANFANG DATA and CQVIP in early June 2022. Three independent authors described the following inclusion criteria for this study: elderly with applied horticultural therapy intervention compared to any other or non-HT intervention. From a total of 3068 records, 34 met the inclusion criteria. After full-text screening, thirteen studies were included. The assessment of risk of bias was conducted using RoBINS-I tool and RoB 2 tool. Comprehensive Meta-analysis 3.3 was used for meta-analysis. Results: The meta-analysis suggested that the mean depression scores of the elderly undergoing horticultural therapy intervention was significantly lower than those without. Larger effects were found for elderly with mean age equal or over 75 years instead of less than 75 years, randomized controlled trials instead of quasi-experimental studies, and for studies with more than 20 participants who receiving horticultural therapy at the same time and the same place instead of equal to or less than 20 horticultural therapy participants.. Conclusions: Evidence supported that horticultural therapy had a significant positive effect on the depressive symptoms reduction outcomes of the elderly. Therefore, it is revealed that the use of horticultural therapy can be considered a part of depressive symptoms reduction programs. Due to the high degree of heterogeneity and the limited number of studies, a future review is warranted to re-examine the effects of horticultural therapy on depressive symptoms among the elderly.